Pengaruh Pola Asuh Otoriter terhadap Kemampuan Interpersonal dan Dukungan Sebaya pada Remaja Sebagai Variabel Moderasi di Kota Bandung - Putra Nurfajri Al Gifari (Epistemik Press, 2021)
This study aims to determine the effect of authoritative parenting on interpersonal skills moderated by peer support in adolescents in Bandung. The participants in this study were (N=400, aged 13-19 years old living with their parents, and domiciled in Bandung) who filled out an instrument containing authoritative parenting measuring tools to measure authoritative parenting, Interpersonal Competence Questionnaire (ICQ) to measure interpersonal skills, and the Social Provosion Scale to measure peer support. Data analysis used was linear regression analysis to determine the effect of authoritative influence on interpersonal skills and peer support on interpersonal skills, and multiple regression analysis with moderation to measure the effect of authoritative parenting on interpersonal skills moderated by peer support. The results of the analysis show that there is an influence of authoritative parenting on interpersonal skills of -0.399 with a significance value of 0.000. There is an effect of peer support on interpersonal skills of 0.281 with a significance value of 0.000. The results of the moderation analysis showed that peer support moderated the influence of authoritative parenting on interpersonal skills. The resulting moderation form is peer support which reduces the influence of authoritative parenting on adolescent interpersonal skills in the city of Bandung.